PREDIKSI PERTUMBUHAN UMKM DI KOTA BANDUNG MENGGUNAKAN METODE AUTOREGRESSIVE INTEGRATED MOVING AVERAGE - Sri Hanifah, Nurul; Gunawansyah (Universitas Sangga Buana, 2024)
This study aims to predict the number of micro, small, and medium enterprises (MSMEs) in Bandung City using the ARIMA (AutoRegressive Integrated Moving Average) method. MSMEs play a crucial role in the local economy, particularly in creating jobs and driving economic growth. Predicting the number of MSMEs is important for understanding future trends to support better planning and policy-making. The data used in this study includes the number of MSMEs in Bandung City from 1990 to 2023. The ARIMA method was chosen for its ability to handle time series data with seasonal patterns and trends and for providing accurate predictions based on historical data. The ARIMA (2,1,0) prediction model was selected as the best model, with model evaluation results showing an MAE value of 666.9431 and a MAPE value of 7.55%. The accuracy of this study using the ARIMA (2,1,0) model is 92.45%. Based on the research findings, the AutoRegressive Integrated Moving Average (ARIMA) method can be used to predict the number of Micro, Small, and Medium Enterprises (MSMEs) in Bandung City.